Weekend hats : 25 knitted caps, berets, cloches, and more - MacDonald, Cecily Glowik (Interweave Press, 2011)
" Embrace the hottest head-turning fashion accessory: the knitted hat The clever designs of Hats 2.0 will have enthusiastic knitters everywhere rejoicing in year-round hat style. Inside you'll find: Expert advice to spark the interests of a variety of skill levels with special attention paid to exploring cables, lace, color, and texture.